Characteristics and verification of a car-borne survey system for dose rates in air: KURAMA-II. (January 2015) - Tsuda, S.; Yoshida, T.; Tsutsumi, M.; Saito, K.
Abstract: The car-borne survey system KURAMA-II, developed by the Kyoto University Research Reactor Institute, has been used for air dose rate mapping after the Fukushima Dai-ichi Nuclear Power Plant accident. KURAMA-II consists of a CsI(Tl) scintillation detector, a GPS device, and a control device for data processing. The dose rates monitored by KURAMA-II are based on the G ( E ) function (spectrum-dose conversion operator), which can precisely calculate dose rates from measured pulse-height distribution even if the energy spectrum changes significantly. The characteristics of KURAMA-II have been investigated with particular consideration to the reliability of the calculated G ( E ) function, dose rate dependence, statistical fluctuation, angular dependence, and energy dependence. The results indicate that 100 units of KURAMA-II systems have acceptable quality for mass monitoring of dose rates in the environment. Highlights: KURAMA-II is a car-borne survey system developed by Kyoto University. A spectrum-dose conversion operator for KURAMA-II was calculated and examined. We examined the radiation characteristics of KURAMA-II such as energy dependence. KURAMA-II has acceptable quality for environmental mass dose rate monitoring.